Solar steam generation on scalable ultrathin thermoplasmonic TiN nanocavity arrays - Mascaretti, Luca; Schirato, Andrea; Zbořil, Radek; Kment, Štĕpán; Schmuki, Patrik; Alabastri, Alessandro; Naldoni, Alberto (Nano Energy, 2021)
Plasmonic-based solar absorbers exhibit complete light absorption in a sub-µm thickness, representing an alternative to mm-thick carbon-based materials most typically employed for solar-driven steam generation. In this work, we present the scalable fabrication of ultrathin plasmonic titanium nitride (TiN) nanocavity arrays that exhibit 90% broadband solar light absorption within 250 nm from the illuminated surface and show a fast non-linear increase of performance with light intensity. At 14 Suns TiN nanocavities reach 15 kg h–1 m–2 evaporation rate and 76% thermal efficiency, a steep increase from 0.4 kg h−1 m−2 and 20% under 1.4 Suns. Electromagnetic, thermal and diffusion modeling of our system reveals the contribution of each material and reactor component to heat dissipation and shows that a quasi-two-dimensional heat dissipation regime significantly accelerates water evaporation. Our approach to ultrathin plasmonic absorbers can boost the performance of devices for evaporation/desalination and holds promise for a broader range of phase separation processes.
CRIS-Team Scopus Importer:2021-02-12
Keywords: Multi-physics modeling; Nanocavity array; Quasi-two dimensional heat transfer; Solar steam generation; Ultrathin plasmonic TiN absorber